Avoiding late preterm deliveries to reduce neonatal complications: an 11-year cohort study - Noémie Bouchet; Angèle Gayet-Ageron; Marina Lumbreras Areta; Riccardo Erennio Pfister; Begoña Martinez de Tejada (BMC, 2018)
Abstract Background Late preterm (LPT) newborns, defined as those born between 34 0/7 and 36 6/7 gestational weeks, have higher short- and long-term morbidity and mortality than term infants (≥37 weeks). A categorization to justify a non-spontaneous LPT delivery has been proposed to distinguish evidence-based from non-evidence-based criteria. This study aims to describe rates and temporal trends of non-spontaneous LPT neonates delivered according to evidence-based or non-evidence-based criteria and to evaluate the number of avoidable LPT deliveries, including severe neonatal morbidity rates and associated risk factors. Methods Retrospective cohort study including all LPT neonates born at a Swiss university maternity unit between January 1, 2002 and December 31, 2012. Trends of LPT neonates and neonatal complications were assessed across time using Poisson regression and risk factors for neonatal complications by logistic regression. Results Among 40,609 singleton live births, 4223 (10.5%) were preterm and 2017 (4.9%) LPT. In the latter group, 26.2% were non-spontaneous (evidence-based: 12.0%; non-evidence-based: 14.2%). The most frequent indications for evidence-based non-spontaneous LPT delivery were severe preeclampsia (51.8%) and abnormal fetal tracing (24.7%). Indications for non-evidence-based non-spontaneous LPT deliveries were hemorrhage (36.2%) and mild preeclampsia (15.7%). LPT birth rates remained stable over time. The rate of neonatal complications after non-evidence-based LPT birth remained high over time (43.8% vs. 43.5% in 2002 and 2012, respectively; P = 0.645), whereas the annual proportion of neonatal complications overall showed a decreasing trend (from 38.0% in 2002 to 33.5% in 2012; P = 0.051). Conclusions LPT birth rates were stable over time, but neonatal complications remained high, particularly after non-evidence-indicated LPT birth. A total of 287 LPT births could have been potentially avoided if an evidence-based protocol for delivery indications had been used. Efforts should be made to avoid non-spontaneous LPT births in order to reduce neonatal complications.